ANALYSIS OF HEAT EXPOSURE PREVENTION ONSTREET VENDORS WORKERS AROUND DIPONEGORO UNIVERSITY CAMPUS SEMARANG - Baju Widjasena; Siswi Jayanti (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Climate change impacts on the increase in ambient temperature. This condition affects human health and environmental conditions. Street vendors have the risk of heat stress because of suffered direct sunlight. Efforts to prevent the effects of heat exposure in developing countries are not optimal. Semarang is residential with the hot climate. The aim of this study was to describe how street vendor prevent them from heat stress Method: The research was a descriptive with a qualitative approach. Data obtained from an in-depth interview with 35 street vendors who work around Diponegoro Univesity Campus. The in-depth questioner consists of how about their process of work, clothe, meal, beverage, and symptom of dehydration. The checklist was used to observed their clothe and shading. Data was analyzed with content analysis Results: Street vendors work under the tree. They suffered heat stress from direct sunlight. They wear loose and clear color of clothing. They have a meal with boullion and much water. They use the tree for shading from direct sunlight. The symptom dehydration that appears was dry throat and feel fatigue. But their urine color was still clear. It’s showed that dehydration has not suffered the street vendors Conclusion: Street vendors have good behavior to prevent heat stress so they are not suffered dehydration